Financial profitability of diversified farming systems: A global meta-analysis - Sánchez, Andrea C.; Kamau, Hannah N.; Grazioli, Francesca; Jones , Sarah K. (Elsevier, 2022)
Diversified farming systems are promoted as a pathway to more sustainable agricultural production. Yet wide scale adoption may be slow because of uncertainty about the viability of farmer livelihoods on diversified farms and entrenched perceptions that monocultures are key to making farming profitable. Here, a global meta-analysis of 3192 effect sizes from 119 peer-reviewed articles provides evidence that diversified farming systems are at least as profitable as simplified farming systems. Our study showed that, on average, total costs, gross income and profits (net income, or gross margin) were higher in diversified systems relative to simplified ones, while the benefit-cost ratio was equivalent. These results held in developed and developing countries and across geographic regions. From a subset of 43 articles reporting labour inputs, we found that labour costs increased in diversified farming systems, but so did gross incomes leading to farm profits equivalent to those in simplified systems and dispelling myths that higher labour requirements undermine the viability of diversification. Our global meta-analysis provides compelling evidence that diversified farming systems are not only viable but actually economically preferable to simplified systems in the wide range of contexts represented in this study. Policies, markets, investments, and value chains need to align with this evidence and promote diversified farming systems for the benefit of farmers and rural economies.